1997
DOI: 10.1159/000021980
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Estrogen Status and Aging on Salivary Flow Rates in Healthy Caucasian Women

Abstract: A comparison of salivary flow rates was made between three groups of female individuals according to their menopausal status. The three groups consisted of healthy, dentate, nonmedicated women (with the exception of the use of estrogen) from the Baltimore Longitudinal Study of Aging. One group consisted of premenopausal women (n = 51), their mean age was 39 years. Another group (n = 26) was perimenopausal with a mean age of 48 years. A third group (n = 76) was postmenopausal with a mean age of 69 years. The gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 33 publications
3
49
0
1
Order By: Relevance
“…However, results are contradictory regarding the effect of use of HT on salivary flow rate [7][8][9][10][11][12][13]. Flow rates have been reported to be higher in perimenopausal women in comparison to postmenopausal women [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, results are contradictory regarding the effect of use of HT on salivary flow rate [7][8][9][10][11][12][13]. Flow rates have been reported to be higher in perimenopausal women in comparison to postmenopausal women [11].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the inorganic and protein composition of saliva changes during the course of pregnancy (Salvolini et al 1998), and in late pregnancy the salivary buffer effect is significantly decreased (Laine & Pienihäkkinen 2000). HRT has been shown to improve the buffering effect of saliva (Laine & Leimola-Virtanen 1996) and, although evidence to the contrary does exist (Streckfus et al 1998, Ghezzi et al 2000, a number of studies (Laine & Leimola-Virtanen 1996, Eliasson et al 2003 have reported an increase in salivary flow rate in association with HRT. Together, these observations suggest that estrogens may play an important role in oral mucosal and salivary gland physiology.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effectiveness of these methods have been debated because they do not reflect structural abnormalities in most cases [3,17]. On the other hand, salivary gland scintigraphy enables a functional evaluation of the salivary glands, making it a valuable tool.…”
Section: Discussionmentioning
confidence: 99%